Evaluation of sulphite in beer and spirits after the new allergen labelling rules - Lachenmeier, Dirk W.; Uta Nerlich, Uta Nerlich (BrewingScience, 2006)
A new European Directive requires food manufacturers to label the potential allergenic substances sulphur dioxide and sulphites if they are used as ingredients at concentrations of more than 10 mg/l in pre-packed foods. FTIR in combination with Partial Least Squares (PLS) regression is presented as a fast (30 samples/hour), simple and inexpensive procedure for the determination of sulphite concentrations in beer (simultaneously with standard parameters like ethanol and original gravity). FTIR/PLS offers considerable advantages when measured against the conventional enzymatic reference procedure and will acquire increasing importance as an efficient high-throughput tool for screening alcoholic beverages. With information gained by FTIR screening, decisions can be made whether additional analyses (with more time-consuming and expensive but more accurate standard procedures) are required. The average concentrations expressed as SO2 were 1.0 mg/l for spirits (n=101) and 4.2 mg/l for beer (n=195). The sulphite concentrations of spirits were found to be significantly lower than those of beer (p<0.0001). The new requirement of allergen labelling presents in few cases a problem for manufacturer of beer and spirits as only 2 spirit (1.9%) and 9 beer samples (4.6%) exceeded the limit of 10 mg/l. However, a labelling of the sulphite concentration had not been carried out in any of these cases.